A RARE COMPLICATION POTT’S PUFFY TUMOR TREATED WITH FRONTOETHMOIDECTOMY: A CASE REPORT - Muhammad Hamza Rana; Muhammad Saleem (Journal of University Medical & Dental College, 2021)
Untreated or undiagnosed frontal sinusitis develops as a subperiosteal abscess in the frontal bone named Pott’s puffy tumor (PPT). Pott’s puffy tumor is a rare complication that needs surgical excision. In this communication, we report a 50-year-old woman presenting with typical signs and symptoms of PPT. CT-Scan and X-ray imaging are the gold standards to measure the extent of tumor and involvement of structures, if any.